Methodology for Using Multi-Temporal Landsat Images to Monitor Urban Growth of Kirkuk Governorate - Tabark Y. Gehad; Nejat Q. Omer; Nada S. Abdulmajeed (Journal of Techniques)
The growth of cities around the world creates difficulties for governments due to the strain it puts on resources and the negative impact on the environment and living conditions for residents. The Kirkuk Governorate has experienced significant urban growth in recent years, causing various environmental, economic, and social issues. the study aims to monitor the growth of Kirkuk Governorate from 1990-2020 using multi-spectral Landsat images to better understand urban development. Landsat-5 TM for 1990, Landsat-7 ETM+ for 2000, Landsat-5 TM for 2010, and Landsat-8 OLI for 2020 were used for this study. The Supervised Maximum Likelihood algorithm was utilized to categorize images into urban and non-urban areas, with accuracy rates ranging from 91.25% to 96.66% between 1990 and 2020. Post-classification change detection analysis was also conducted to observe changes in urban growth, revealing that the studied city expanded from 46.96 km2 to 193.25 km2 over 30 years. Over the past thirty years, the urban area of Kirkuk Governorate has increased while the non-urban area has decreased. This is due to factors such as population growth, political changes, and economic development. This study provides valuable information about this urban growth and can be used as a foundation for future studies on the region's socioeconomic and environmental changes.